Foreign entry strategies: strategic adaptation to various facets of the institutional environments - Ferreira, Manuel Portugal (2021)
A comprehensive model of foreign entry strategies by multinational enterprises (MNEs) is developed in this paper, and a theory is proposed on how the entry strategy is likely to be determined in the interface between internal and external pressures for both conformity and legitimacy. In contrast to a selection rationale, an adaptation argument is developed, through which we enhance our understanding of the various facets of the institutional environment and the constraints MNEs encounter in their internationalization strategies.